2018
DOI: 10.2134/jeq2018.02.0076
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil to Mitigate Antibiotics in the Environment Due to Release of Wastewater Treatment Plant Effluent

Abstract: With low levels of human antibiotics in the environment due to release of wastewater treatment plant (WWTP) effluent, concern is rising about impacts on human health and antibiotic resistance development. Furthermore, WWTP effluent may be released into waterways used as drinking water sources. The aim of this study was to analyze three antibiotics important to human health (sulfamethoxazole, ofloxacin, and trimethoprim) in soil and groundwater at a long‐term wastewater reuse system that spray irrigates effluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
3
6
0
Order By: Relevance
“…This intervention, though with positive developmental outcomes (food security, livelihoods) [ 27 ], may have unintended public health-related consequences for the environment, animals, and humans [ 11 ]. In addition, agroecological practices (organic manure, livestock biodiversity, scavenging feed resource base) [ 7 , 28 , 29 ], environmental elements (water, soil, wildlife, biocides) [ 30 , 31 , 32 ] as well as hygiene and sanitation levels (human sewage, wastewater, biosecurity) [ 33 , 34 , 35 , 36 , 37 ] within the SPPS, may act as reservoirs for the dissemination of AMR bacteria to the chickens which may eventually be transferred to humans through the food chain [ 38 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This intervention, though with positive developmental outcomes (food security, livelihoods) [ 27 ], may have unintended public health-related consequences for the environment, animals, and humans [ 11 ]. In addition, agroecological practices (organic manure, livestock biodiversity, scavenging feed resource base) [ 7 , 28 , 29 ], environmental elements (water, soil, wildlife, biocides) [ 30 , 31 , 32 ] as well as hygiene and sanitation levels (human sewage, wastewater, biosecurity) [ 33 , 34 , 35 , 36 , 37 ] within the SPPS, may act as reservoirs for the dissemination of AMR bacteria to the chickens which may eventually be transferred to humans through the food chain [ 38 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…This intervention, though with positive developmental outcomes (foo livelihoods) [27], may have unintended public health-related consequences fo ronment, animals, and humans [11]. In addition, agroecological practices (o nure, livestock biodiversity, scavenging feed resource base) [7,28,29], environ ments (water, soil, wildlife, biocides) [30][31][32] as well as hygiene and sanitation man sewage, wastewater, biosecurity) [33][34][35][36][37] within the SPPS, may act as re the dissemination of AMR bacteria to the chickens which may eventually be to humans through the food chain [38] (Figure 1). The production performance of improved chicken genetics for dual-pur egg) functions within SPPS in Nigeria (FUNAAB Alpha, Noiler, ShikaBrown, roiler), and in some other African countries (Ethiopia, Tanzania) have been under on-station and on-farm conditions [24,25,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kibuye et al (2019) found that concentrations of naproxen and acetaminophen were several orders of magnitude lower in receiving groundwater than in Penn State WRF effluent that was spray irrigated onto the Living Filter. At the same site, Franklin et al (2018) found that trimethoprim in effluent degraded quickly through the Living Filter and did not reach groundwater. However, the same study found that ofloxacin and sulfamethoxazole did not degrade as readily through the soil profile and that sulfamethoxazole was the most mobile and had the highest concentrations in groundwater compared with the other antibiotics.…”
Section: Ecological Risksmentioning
confidence: 99%
“…This study demonstrates the effectiveness of Fe and Al (oxy)hydroxides to remove As from water. Franklin et al (2018) investigated the fate of antibiotics present in wastewater effluent. Most municipal treatment plants are not able to completely remove pharmaceuticals from the waste stream, leading to low concentration of these compounds in the environment.…”
Section: Regulating Studies: Roles Of Soil Chemistry In Influencing Tmentioning
confidence: 99%